Perlombaan islami sebagai sarana peningkatan nilai religius pada program kerja kkn mahasiswa di dusun pohbener - Aldina, Ruhi Salisya (Maliki Interdisciplinary Journal, 2025)
The role of Real Work Lectures (KKN) in improving community religious values through Islamic competitions in Pohbener Hamlet. This activity involves collaboration between the hamlet government, religious leaders and the community, and involves students as implementers. The research results show that Islamic competitions not only function as entertainment, but also as an educational tool that can increase individual spiritual awareness and religiosity. This activity also contributes to the formation of participants’ character through values such as honesty and cooperation. This research concludes that the Islamic competition program in KKN is relevant and strategic in an effort to increase community religious values and strengthen student service.